ANALISIS KEAKTIFAN MANAJEMEN RISIKO DALAM MENENTUKAN KEBIJAKAN STRUKTUR MODAL, KEPUTUSAN PEMBERIAN KREDIT, TINGKAT RISIKO DAN PROFITABILITAS BANK UMUM - Sudarsono, Heri (Derivatif : Jurnal Manajemen, 2020)
This study aims to analyze the activeness of bank risk management in influencing the capital structure policy, lending decisions, the level of bank profitability and risk. The samples used in this study were 4 banks that met the requirements in this study. The method used in this study was SEM (Structural Equation Modelling). Based on the research results, it can be concluded that the capital factor and risk management factors have a positive effect on the lending factor. Risk factors have negative effect on lending factors, capital factors and risk management factors have no positive effect on profitability factors. Risk factors have a positive effect on profitability factors, Lending factors have no positive effect on profitability factors, capital factors and risk management factors have positive effects on risk factors. Risk Management Factors and Profitability Factors have a positive effect on Capital Structure Factors, Risk Factors do not have a negative effect on Capital Structure Factors, Capital Factors and Lending Factors have no positive effect on Capital Structure Factors.Keywords: Risk Management, Capital Structure, Lending, Profitability, Risk